2020
DOI: 10.1016/j.ejvs.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – A Systemic Evaluation of the Costs of Elective EVAR and Open Abdominal Aortic Aneurysm Repair Implies Cost Equivalence

Abstract: WHAT THIS PAPER ADDS The cost effectiveness of endovascular aneurysm repair (EVAR), and therefore EVAR as the primary option for elective abdominal aortic aneurysm repair, remains a matter of debate. However, data used as the rationale for these conclusions are impeded by time dependent effect modification, confounded by indication and asymmetric evaluation of re-interventions after repair, with an extensive focus on graft related re-interventions. In this article an instrumental variable analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…1 Pathogenic variants in 5 genes cause Loeys-Dietz syndrome, also termed transforming growth factor-β vasculopathies. 1-3,5,6 Some pathogenic variants in Loeys-Dietz syndrome genes, in particular TGFBR1 and TGFBR2 , may have earlier onset TAD. 7 All the Loeys-Dietz syndrome genes confer a risk for aortic involvement distal to the aortic root along with branch vessel and intracranial aneurysms.…”
Section: Aneurysmsmentioning
confidence: 99%
“…1 Pathogenic variants in 5 genes cause Loeys-Dietz syndrome, also termed transforming growth factor-β vasculopathies. 1-3,5,6 Some pathogenic variants in Loeys-Dietz syndrome genes, in particular TGFBR1 and TGFBR2 , may have earlier onset TAD. 7 All the Loeys-Dietz syndrome genes confer a risk for aortic involvement distal to the aortic root along with branch vessel and intracranial aneurysms.…”
Section: Aneurysmsmentioning
confidence: 99%
“…Whilst there has been some suggestions that EVARs are associated with higher costs, a recent review by Bulder et al . demonstrated a cost equivalence between EVAR and OR 15 . One important determining factor of this was the length of post‐operative admissions, with patients who underwent OR demonstrating longer admission lengths to both ICU and surgical wards 15 .…”
Section: Discussionmentioning
confidence: 99%
“…15 One important determining factor of this was the length of postoperative admissions, with patients who underwent OR demonstrating longer admission lengths to both ICU and surgical wards. 15 Whilst our review did not find a significant difference in the length of admission to ICU, those undergoing endovascular repair did demonstrate a significantly shorter total length of admission. This inevitably has implications on the costs and resources associated with post-operative care, although this was not further explored given the scope of this review.…”
Section: Open Versus Endovascular Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the considerable number of performed studies, the exact percentages of reinterventions in literature and our study are hardly comparable since each study used other criteria for describing reinterventions [17] and reported other follow-up periods. Nevertheless, reporting reinterventions at the national level might be valuable to evaluate the nationwide impact of the reinterventions following EVAR and OSR, especially since reinterventions significantly raise the costs of AAA repair [19,20]. Although we could only report on a large sample of nationwide data within this study design, which had similar patient characteristics (age and sex) when comparing the administrative healthcare data with the DSAA, this study revealed that about 1 in 10 patients received a reintervention within 12 months following EVAR and OSR.…”
Section: Table 3cmentioning
confidence: 99%